Розвиток людського потенціалу в університетських бізнес-інкубаторах - Плинокос, Д. Д.; Москаленко, А. О.; Москаленко, А. А.; Plynokos, D.; Moskalenko, A. (ЦНТУ, 2018)
В статті досліджується розвиток людського та інтелектуального потенціалу в середовищі бізнес-інкубаторів, які діють на базі вищих навчальних закладів. Розглянуто сутність поняття “бізнес-інкубатор” та його розвиток в системі національної економіки. Розкрито основну модель взаємодії університетів, бізнес-середовищ (інкубаторів) та держави. Проаналізовано основні тенденції зміни кількості студентів закладів вищої освіти та виявлено основні причини даної тенденції. Розглянуто тенденції та процеси розвитку бізнес-інкубаторів в системі закладів вищої освіти. В статье исследуется развитие человеческого и интеллектуального потенциала в среде бизнес-инкубаторов, которые действуют на базе высших учебных заведений. Рассмотрена сущность понятия "бизнес-инкубатор" и его развитие в системе национальной экономики. Раскрыта основная модель взаимодействия университетов, бизнес-среды (инкубаторов) и государства. Проанализированы основные тенденции изменения количества студентов высших учебных заведений и выявлены основные причины данной тенденции. Рассмотрены тенденции и процессы развития бизнес-инкубаторов в системе учреждений высшего образования. The main purpose of this article is to do a research of the development of human potential in a business incubator environment based on the universities. The processes of interaction between universities, business and the state are considered in the article. The tendency of changing the number of students of the universities as the basis for the formation of human potential was investigated. The development of an innovative national economy takes place in close connection with the development of scientific and technical activities in the universities. These types of cooperation are presented as the forms of internships, training on the enterprise basis in Ukraine. However, this interaction can also be executed at the university-business-state level. The main purpose and the basis of this model is that the university acts as a core of innovation in a modern society, which works closely with business processes. Thus, the state receives a qualitatively formed human potential, which has developed fundamentally within business incubators. However, there is a decrease in the number of students of university around the whole country. The main reasons of this are that most of the future students are going to enter the universities in the EU, and most of them plan to stay there to work. This situation can be greatly improved by involving business representatives in the scientific and educational processes through the creation and operation of business incubators as an important and indispensable provider of quality human potential. It was found out that the development of business incubators is an integral part and one of the main components of the innovative development of the national economy. The interaction of universities, business and the state is the key to the rapid development of the state’s human potential. The business incubator as an intermediary between universities and the state is a significant structural unit for the development of scientific and educational researches, getting new knowledge and experience of cooperation with enterprises. There are all the favorable conditions for the development and improvement of the own potential of each of its participants within this business environment, forming the overall indicator of human development of the state.
Развитие человеческого потенциала в университетских бизнес-инкубаторах
The Human Potential Development in the University Business Incubators
Keywords: бізнес-інкубатор; заклади вищої освіти; людський потенціал; інтелектуальний потенціал; бизнес-инкубатор; высшие учебные заведения; человеческий потенциал; интеллектуальный потенциал; business incubator; institutions of higher education; human potential; intellectual potential